Headache in the Neurological Emergency Department—High Degree of Inadequate Documentation Calls for Structured Assessments - Rimmele, Florian; Janke, Josephine; Kropp, Peter; Kasch, Ramon; Walter, Uwe; Jürgens, Tim P. (Frontiers in Neurology, 2022)
Headaches are a frequent reason for presentation to the emergency department (ED) and can pose a great challenge for the attending physicians. First and foremost, the distinction between a primary and secondary headache with potentially life-threatening implications can be difficult. Moreover, it often occurs that no specific headache diagnosis is made at discharge from the ED. Therefore, in this present retrospective cross-sectional study, all patients who presented to the emergency department of the Department of Neurology at Rostock University Medical Centre with the main symptom of headache between November 2013 and November 2016 were examined and the extent to which warning symptoms ("red flags") for a secondary headache as well as symptoms necessary for a correct headache diagnosis according to the ICHD-3 classification were recorded and documented. We could show that documentation of red flags and clinical characteristics is inadequate and does not allow proper diagnostic categorization. To facilitate concise documentation and rapid decision making we suggest a structured and standardized form for documenting the headache history and red flags in the ED.